The justice of DikÃª on the forms and significance of dispute settlement by arbitration in the Iliad - Malamis, Daniel Scott Christos (Rhodes University, Faculty of Humanities, School of Languages, 2011)
This thesis explores the forms and significance of dispute settlement by arbitration, or 'Î´Î¯ÎºÎ·', in the Iliad. I take as my focus the 'storm simile' of Iliad XVI: 384-393, which describes Zeus' theodical reaction to corruption within the Î´Î¯ÎºÎ·-court, and the 'shield trial' of Iliad XVIII: 498-508, which presents a detailed picture of such a court in action, and compare the forms and conception of arbitration that emerge from these two ecphrastic passages with those found in the narrative body of the poem. Analysing the terminology and procedures associated with dispute settlement in the Iliad, I explore the evidence for the development of an 'ideology of Î´Î¯ÎºÎ·', that valorises arbitrated settlement as a solution to conflict, and that identifies Î´Î¯ÎºÎ· as a procedure and a civic institution with an objective standard of fairness: the foundation of a civic concept of 'justice'. I argue that this ideology is fully articulated in the storm simile and the shield trial, as well as Hesiod's Works and Days, but that it is also detectable in the narrative body of the Iliad. I further argue that the poet of the Iliad employs references to this ideology, through the narrative media of speech and ecphrasis, to prompt and direct his audience's evaluation of the nature and outcome of the poem's central conflict: the dispute of Achilles and Agamemnon.
Keywords: Homer -- Iliad; Epic poetry, Greek -- History and criticism; Law in literature; Justice in literature; Dispute resolution (Law); Arbitration and award (Greek law)